2004
DOI: 10.1113/jphysiol.2003.052514
|View full text |Cite
|
Sign up to set email alerts
|

Sudden neonatal death in PACAP‐deficient mice is associated with reduced respiratory chemoresponse and susceptibility to apnoea

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP)-deficient mice are more prone to sudden death during postnatal weeks 1-3 than wild-type littermates. Given that PACAP is localized in brainstem regions associated with respiratory chemosensitivity, we examined whether PACAP-null neonates have reduced respiratory responses to hypoxia and hypercapnia. Using unrestrained, whole-body, flow-through plethysmography we found that, by postnatal day 4, the PACAP-null neonates had significantly reduced ventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 50 publications
2
67
1
Order By: Relevance
“…Recently, it has been suggested that PACAPdeficient mice suffer from reduced ventilation and a blunted response to hypoxia. 31 Taking into account these findings may lead to the assumption that bronchoconstriction promotes secondary pulmonary hypertension in PAC1-deficient mice. However, the observation that hypoxia in our PAC1-mutant mice occurred in rather late stages of the disease may account for the opposite, ie, the existence of primary pulmonary hypertension in PAC1-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that PACAPdeficient mice suffer from reduced ventilation and a blunted response to hypoxia. 31 Taking into account these findings may lead to the assumption that bronchoconstriction promotes secondary pulmonary hypertension in PAC1-deficient mice. However, the observation that hypoxia in our PAC1-mutant mice occurred in rather late stages of the disease may account for the opposite, ie, the existence of primary pulmonary hypertension in PAC1-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, other factors could influence testicular aging in this setting. It has been shown that PACAP Ϫ/Ϫ mice present numerous phenotypes, including high mortality and reduction in glucose levels [6]. In addition, PACAP has some structural homology with vasoactive intestinal peptide (VIP) and in a more limited fashion with GHRH, although testicular GnRH receptor expression seems to play a less important role than originally proposed.…”
mentioning
confidence: 91%
“…PACAP is central to the early development of the central nervous system. Null mutant mice lacking PACAP exhibited hypoventilation during the neonatal period and were prone to sudden death preceded by prolonged apneas between 1 and 3 wk after birth (18). Furthermore, hypothermia worsened the respiratory depression.…”
Section: Mutant Newborn Mice With Abnormal Rhythmogenesismentioning
confidence: 99%
“…Furthermore, studies have shown that PACAP is involved in chemosensitivity to oxygen. Null mutant newborn mice lacking the gene for PACAP had blunted ventilatory responses to hypoxia (18). In vitro data indicated that PACAP stimulated the carotid bodies (17).…”
Section: Mutant Newborn Mice With Abnormal Chemosensitivitymentioning
confidence: 99%
See 1 more Smart Citation